CHRONIC POST-SURGICAL PAIN AFTER TOTAL KNEE ARTHROPLASTY-RISK FACTORS AND PREVENTION - Srećković, Svetlana (Medicinski podmladak, 2024)
Chronic post-surgical pain (CPSP) is one of the frequent complications affecting patients' quality of life which additionally increases economic and healthcare burdens after surgery. The incidence of CPSP depends on the type of surgery with wide variability among surgeries. Chronic diseases, lifestyle changes, and increased life span lead to increasing surgeries performed worldwide, especially in orthopedics. Total knee arthroplasty (TKA) is a standard orthopedic procedure performed in end-stage knee osteoarthritis to improve the quality of life and decrease pain.  Different pain management strategies are suggested to provide adequate analgesia and prevent chronic pain after TKA. CPSP after TKA is an almost three-fold risk compared with other surgeries and the prevalence is also higher than after total hip arthroplasty. The prevention and treatment of CPSP after TKA are crucial not only because affecting the quality of life and causing dissatisfaction but becoming one of the reasons for revision surgery. The early identification of risk factors for CPSP after TKA is important to guide the development of preventive treatment strategies that may also improve post-surgical outcomes.
Keywords: chronic pain; risk factors; total knee arthroplasty